(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Laterites used mostly for construction in the tropics can sometimes be problematic due to insufficient geotechnical properties. This explores the potential benefits of incorporating coir reinforcement into laterite. Coir, derived from coconut husk fibers is a sustainable, renewable and abundant resource that has high tensile strength, low density, and good resistance to decay. Geotechnical properties such as Liquid limit (LL), Plastic limit, Plasticity index, Maximum dry density, Optimum moisture content (OMC) and California bearing ratio (CBR) of the laterite were determined before reinforcement. The coir was cut into different lengths (3 to 5 cm) and added to the laterite at different percentages (0.25 to 1.5% at 0.25% increment). The geotechnical properties of the reinforced soil were determined and the results were analyzed using analysis of variance and fuzzy logic. The CBR of the reinforced soil was predicted using fiber content, OMC, and LL The precision of the fuzzy logic model was obtained by comparing the model results with the actual experimental results. Addition of fiber at 0.25% was found to be the optimum as it increased the CBR of the soil by 27.24% and reduced the Liquid limit by 15.47%. The fuzzy logic prediction has a RMSE of 1.18, MAPE of 4.68% and R-squared of 0.98 which shows that the fuzzy logic model is satisfactory. The study concluded that coir is a potential reinforcement for improving the geotechnical properties of laterite and that Fuzzy Logic can be used to predict the CBR of coir reinforced laterite.